Regional disparities in food security and depression among single-person households in the Republic of Korea - Seong-Ah Kim; Seul Ki Choi (BMC, 2023)
Abstract Background Single-person households constitute over 40% of all households in the Republic of Korea and are more vulnerable to food insecurity and depression than multi-person households. There is a lack of research on examining whether regional characteristics are associated with the degree of food insecurity and depression among single-person households. This study aimed to examine the regional disparities in food security and depression among single-person households in the Republic of Korea. Methods A total of 227,873 adults from the 2019 Korean Community Health Survey was included in the analysis. According to population density and poverty rate, the residence of the participants was classified into four regions: metropolitan areas with high population density were classified into areas with low poverty rates (Region 1) and high poverty rates (Region 2), and provinces with low population density were classified into areas with low poverty rates (Region 3) and high poverty rates (Region 4). Using a single item of household food security, those who had experienced a lack of food due to financial difficulties over the past year were classified as food insecure. Depression was measured using the Patient Health Questionnaire-9. Odds ratios and 95% confidence intervals (CI) for the risk of food insecurity and depression according to regional characteristics were calculated after adjusting for potential confounding variables. Results After adjusting for confounding variables, single-person households in regions with high population density, Regions 1 and 2, had 1.16 times (95% CI = 1.04-1.30) and 1.43 times (95% CI = 1.27-1.61) higher odds of food insecurity, respectively, compared to those in Region 4. Single-person households in regions with low poverty rates, Regions 1 and 3, had 1.54 times (95% CI = 1.34-1.77) and 1.21 times (95% CI = 1.01-1.46) higher odds of depression, respectively, than those in Region 4. Among those who lived alone, the middle-aged, having low income, receiving livelihood benefits, or having a low educational attainment had higher odds of experiencing both food insecurity and depression than their counterparts. Conclusions As the risk of food insecurity and depression in single-person households differs according to regional characteristics, local governments need to implement policies for single-person households in consideration of these distinct characteristics.